Determinan Struktur Modal Inovasi dan Nilai Perusahaan (Studi pada Industri Manufaktur di Bursa Efek Indonesia) - Sujono -; M.S. Idrus; Made Sudarma; Solimun - (Jurnal Aplikasi Manajemen, 2012)
The purpose of this research is to develop a model of the determinants of capital structure, innovation and firm value of the psychological aspect, which is controlled by company-specific variables and blockholder ownership structure. This research was conducted in manufacturing industry in Indonesian Stock Exchange on the company. Partial Last Square is used as the method of analysis. There were twenty two companies which were analyzed The study found that capital structure determined by an overconfidence attitude of managers who are supported by company’s internal factors. In addition to determining capital structure, managers’ overconfidence also plays a role in the innovation decision and the firm value determination. Financing innovation in is much more determined by internal sources. The value of manufacturing company in Indonesia is more determined by internal factors and the structure of blockholder ownership.Keywords: overconfidence, capital structure, innovation, blockholder, internal factors, firm value.